2017
DOI: 10.3389/fgene.2017.00035
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Loss in Identity, De-Differentiation, and Trans-Differentiation of Islet β-Cells in Type 2 Diabetes

Abstract: The two main types of diabetes mellitus have distinct etiologies, yet a similar outcome: loss of islet β-cell function that is solely responsible for the secretion of the insulin hormone to reduce elevated plasma glucose toward euglycemic levels. Type 1 diabetes (T1D) has traditionally been characterized by autoimmune-mediated β-cell death leading to insulin-dependence, whereas type 2 diabetes (T2D) has hallmarks of peripheral insulin resistance, β-cell dysfunction, and cell death. However, a growing body of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 57 publications
0
72
0
3
Order By: Relevance
“…Furthermore, the number of Taf4-expressing BCs did not increase between 34 and 55 weeks arguing against proliferation of non-recombined BCs. Alternatively, Taf4-expressing BCs may arise from trans-differentiation of alpha cells or other islet populations into BCs as has been previously described, for example under conditions of reduced BC-mass [30][31][32][33] , one of the consequences of Taf4 inactivation. Notwithstanding the mechanisms involved, these data showed that despite reduced BC mass through increased apoptosis and an ensuing elevated glycaemia, the BC population was only partially and slowly replaced by newly generated BCs.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Furthermore, the number of Taf4-expressing BCs did not increase between 34 and 55 weeks arguing against proliferation of non-recombined BCs. Alternatively, Taf4-expressing BCs may arise from trans-differentiation of alpha cells or other islet populations into BCs as has been previously described, for example under conditions of reduced BC-mass [30][31][32][33] , one of the consequences of Taf4 inactivation. Notwithstanding the mechanisms involved, these data showed that despite reduced BC mass through increased apoptosis and an ensuing elevated glycaemia, the BC population was only partially and slowly replaced by newly generated BCs.…”
Section: Discussionmentioning
confidence: 89%
“…The molecular mechanisms involved particularly at the transcriptional level are however not fully understood 30,32,[45][46][47] . In type 2 diabetes, hyperglycaemia seems to induce BC dedifferentiation with diminished expression BC function genes and key BC transcription factors, but expression of BC forbidden genes and it may involve reversion to a Ngn3-expressing precursor state as a prerequisite to trans-differentiation to alpha or delta cells 33,40,48 . BC transdifferentiation upon loss of Taf4 occurred rapidly in absence of chronic hyperglycaemia and was characterized by loss of BC markers, but not by up-regulated expression of forbidden genes and it did not require passage via a progenitor state.…”
Section: A Model For Beta Cell Trans-differentiationmentioning
confidence: 99%
“…Pancreatic islets are metabolically limited in their ability to store lipids. The possible mechanisms of irreversible β-cell demise in the setting of T2D progression involve interactions among many branches of cellular metabolism, including inflammation, severe endoplasmic reticulum (ER) and oxidative stress, de novo ceramide synthesis, mitochondrial injury, compromised autophagy, epigenetic changes, β-cell de-differentiation, and loss of β-cell identity [29,30]. Increases in circulating plasma levels of FAs and disturbances in lipid homeostasis emphasize the importance of free FAs during β-cell adaptation and the metabolic control of diabetes [29].…”
Section: Lipoadaptation and Lipotoxicity: Two Sides Of The Same Coinmentioning
confidence: 99%
“…The most plausible mechanism to explain the effects of gluco-and lipotoxicity on pancreatic islet decompensation in T2D is massive β-cell death. However, recent genetic and epigenetic studies indicate that both β-cell demise and the loss of pancreatic endocrine cell identities may be major causes of the development of obesity-related T2D [26][27]. Alterations of cell proliferation, survival, transdifferentiation, dedifferentiation, or migration that are related to remodeled cell-cell contacts may result in the reorganization of pancreatic islet microarchitecture.…”
Section: Metabolic Stress Dna Methylation and Compromised Identity mentioning
confidence: 99%